PENGARUH MEDIA KONKRET TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA KELAS II SD NURUL FATHIMIYAH BANDAR KLIPPA TAHUN AJARAN 2021/2022 - Zulvia Misykah; Dewi Sartika Panggabean (Universitas Negeri Medan, 2022)
Abstract: The Influence of Concrete Media on Students' Learning Result in Mathematics Lessons in Class II SD Nurul Fathimiyah Bandar Klippa Academic Year 2021/2022. This study aims to determine the effect of concrete media on the learning result of class II students at SD Nurul Fathimiyah, class IIa as an experimental class with 25 students and class IIb as a control class with 25 students. The data collection technique used a written test of math problems, hypothesis testing in this study used the Independent sample t-test. Based on the results of the study, it can be concluded that student learning outcomes in mathematics lessons on multiplication material after using concrete media obtained an average value of 85.00, and after using conventional learning an average value of 75.00. for second grade students of SD Nurul Fathimiyah